2017
DOI: 10.11648/j.cmr.20170601.13
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Satisfaction with Institutional Delivery Service in Public Health Facilities of Omo Nada District, Jimma Zone

Abstract: Assessment of client satisfaction has become an administrative and a practical reality; it is important measure of the quality of services. Satisfaction studies provide feedback on how well the service is functioning according to clients' perception and what changes might be required to meet clients' expectation. Satisfaction affects service utilization; satisfied mothers will have optimum utilization of delivery service. This study assessed satisfaction with institutional delivery service and factors affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 8 publications
9
37
3
Order By: Relevance
“…In this study, the overall satisfaction of mothers on delivery service was found to be 88%, which was comparable to the study conducted in Wolayita Zone (82.9%), Debremarkos town (81.7%) and Assela Hospital (80.7%) [9,11,17]. However, it was higher than the study, which was conducted in Jimma (77%) [19] and Amhara Referral Hospitals (61.9%) [12] in Ethiopia and South Africa (51.9%) and Kenya (56%) in Africa [9,10]. The difference with the above finding may be because of a real difference in the quality of services provided, expectation of mothers or the type of health facilities.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, the overall satisfaction of mothers on delivery service was found to be 88%, which was comparable to the study conducted in Wolayita Zone (82.9%), Debremarkos town (81.7%) and Assela Hospital (80.7%) [9,11,17]. However, it was higher than the study, which was conducted in Jimma (77%) [19] and Amhara Referral Hospitals (61.9%) [12] in Ethiopia and South Africa (51.9%) and Kenya (56%) in Africa [9,10]. The difference with the above finding may be because of a real difference in the quality of services provided, expectation of mothers or the type of health facilities.…”
Section: Discussionsupporting
confidence: 70%
“…Studies from developing countries show that satisfaction with services had a negative association with the amount of time women spent at the health facility before childbirth [17]. The educational level of women in different studies and settings has demonstrated positive, negative or nil association with satisfaction during delivery services [18,19]. Other identified factors that influenced satisfaction with childbirth services are: having clean and orderly labour rooms and women-friendly delivery processes, such as having been prepared in advance for what to expect during the labour/postpartum/breast feeding period; involvement in the decision-making process; having a birth plan and being able to follow it; having pain relief during labour; having a birth companion and respectful care providers; receiving help from care providers inperforming self and neonate'scare; and experiencing less symptoms in the postpartum period [20][21][22][23][24][25].…”
Section: Journal Of Public Management Researchmentioning
confidence: 99%
“…Moreover, educated mothers might know service quality standards and might compare the services they received with the standard (24). This institution based cross-sectional study depicted that maternal satisfaction on delivery services was signi cantly associated with ANC follow-up which is inline with the ndings of other studies (15,18,23,27). ANC follow-up might give mothers a continuum of care from the ante natal to the post-partum period which will grant mothers all the necessary information about birth preparedness and information related to the current pregnancy (28).…”
Section: Discussionsupporting
confidence: 81%
“…Concerning sample size, the sample size of the individual studies ranged from 256 to 736. The highest and lowest prevalence (95%) and (19%) of women satisfaction towards existing labour and delivery services were reported in studies conducted in Wolaitta Soddo Town, Southern Nations, Nationalities, and Peoples Region and Addis Ababa, respectively [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (table 2).…”
Section: Resultsmentioning
confidence: 99%